Consumer sentiment during the COVID-19 pandemic - Dzung Bui; Lena Dräger; Bernd Hayo; Giang Hong Nghiem (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2020)
We analyze consumer sentiment with a novel survey of Thai and Vietnamese consumers conducted in May 2020, that is, shortly after the end of the immediate lockdown due to the COVID-19 pandemic. In a randomized control trial, we expose subgroups of the survey respondents to four different information treatments: (1) how their country ranks in a global survey on agreement or disagreement with the government's response to COVID-19, (2) how the country compares in a global survey on the appropriateness of the general public's reaction to the pandemic, (3) the negative unemployment outlook due to the pandemic, and (4) the positive effects of social distancing for the spread of the virus. First, our results show that consumers are more optimistic if they expect higher GDP growth and trust the government in dealing with the crisis, whereas having stronger concerns about their household's financial situation due to COVID-19 is related to less optimistic sentiment. Second, we find that the information treatments only weakly affect consumer sentiment. However, consumer sentiment is strongly affected by treatment (1) and (2) when they go against respondents' previously held views. Finally, we discover large differences between the two countries.
Keywords: E71; H12; I12; I18; Z18; 330; Consumer sentiment; COVID-19; randomized control trial (RCT); survey experiment; government trust; macroeconomic expectations; Thailand; Vietnam